40 Pilot randomised control trial of default technology configurations to block cellphone use while driving among teen drivers. (19th September 2017) - Delgado, M Kit; Huang, Hanlan; Halpern, Scott; Buttenheim, Alison; Wiebe, Doug; Branas, Charles; Saulsgiver, Kathryn
Abstract : Purpose: Distracted driving is the largest increasing cause of motor vehicle crash deaths in the U.S prompting the need for interventions. Methods/approach: We conducted an 8 week pilot randomised control trial of default technology configurations that block cellphone use while driving. We enrolled licensed teens who admitted to texting while driving. Participants installed a windshield-mounted device that could block phone use while driving. Data on cellphone use, vehicle speed, and trip time were collected. Participants completed a 4 week baseline monitoring phase followed by a 4 week intervention phase in one of four arms: 1) monitoring only; 2) 'opt-in' blocking; 3) 'opt-out' blocking; and 4) 'opt-out' blocking with parental notification. Using generalised linear models, we measured the difference in phone unlocks and minutes of phone use per hour of driving between the intervention and baseline periods relative to the monitor only arm. Results: We enrolled 32 participants; 8 randomised to each arm. During the baseline period the teen drivers had 3.3 (IQR 1.5–5.4) unlocks per hour and 5.89 min (SD 5.88) of non-call phone use per hour of driving. There were less minutes of phone use per hour in the opt-out blocking arm (−2.06 95%; CI: −4.07, –0.09) and opt-out blocking with notification arm (−1.92; 95%: CI; −3.90, 0.44). The effect on unlocks per hour was less strong with −0.71 (95% CI: −2.24. 1.10) in the opt-out blocking arm and −0.43 (95% CI: −1.96, 1.10) in the opt-out blocking with notification arm. Conclusions: Opt-out activation of cellphone blocking appears promising for reducing the amount of time the phone is unlocked while driving, but additional strategies may be needed to reduce handheld engagement among teen drivers. Significance and Contributions to Injury and Violence Prevention Science: We demonstrated the feasibility of a novel approach for testing scalable smartphone-based interventions for reducing cellphone use while driving.